Pre-pandemic predictors of parental substance use during COVID-19 - Greenwood, Christopher J.; Letcher, Primrose; Hutchinson, Delyse M.; Macdonald, Jacqui A.; Grigg, Jasmin; Boden, Joseph M.; Toumbourou, John W.; Olsson, Craig A. (Frontiers in Child and Adolescent Psychiatry, 2025)
AimsTo examine pre-pandemic predictors of parent substance use during COVID-19 in Australia, where some of the longest periods of public health restrictions in the world occurred.MethodsWe used data from the Australian Temperament Project Generation 3 Study on 560 parents (59% female) who completed COVID-19 specific surveys (2020/2021), including assessment of alcohol, tobacco, and illicit substance use. Comprehensive pre-pandemic assessments were conducted during the postpartum period when offspring turned 1-year of age (2012–2018), including 33 indicators spanning parent and child factors (individual, relational, and contextual).ResultsDuring the pandemic, 39% of parents reported drinking alcohol 3-to-4 days per week or more, 12% used tobacco, and 6% used illicit substances. In Least Absolute Shrinkage and Selection Operator (LASSO) logistic regression models, a variety of pre-pandemic predictors [k] were identified across alcohol (AUC = 0.72, k = 2; OR = 0.92–2.03), tobacco (AUC = 0.96, k = 10; OR = 0.61–4.21), and illicit substance use (AUC = 0.78, k = 2; OR = 1.44–1.60). The strongest predictors were pre-pandemic use of the same substance (OR = 1.60–4.21). While few other predictors were identified for alcohol and illicit substance use, several family characteristics predicted tobacco use.ConclusionsResults indicated that parents engaging in alcohol, tobacco and illicit drug use in our cohort reported strong continuity of use from before, to during the COVID-19 pandemic in Australia. This highlights the importance of public health initiatives that provide accessible substance use support and treatment options to parents during periods of public health emergencies. Further, enriched population interventions targeted across socioeconomic and family contexts may be important in identifying risk, particularly for tobacco use.